PERAN DESAIN LAYOUT DAN PEMELIHARAAN FASILITAS PRODUKSI DALAM MENUNJANG KELANCARAN PROSES PRODUKSI PADA RAJA MIE COKRO KOTA PROBOLINGGO - Dedi Joko Hermawan (UNIVERSITAS PGRI MADIUN, 2018)
The production process is a series of processes or steps involved in producing a good product in a manufacturing company. To achieve the level of efficiency and effectiveness in the production activity is necessary to note several factors that influence the course of the production process. Design layout and maintenance of production facilities being part of the factor. Where the design layout is a preparation of the layout of production facilities such as machinery and equipment or other equipment used in production activities. While maintenance is an activity to maintain or keep the production facilities to keep them in good condition. The purpose of this study was to determine whether the design layout and maintenance of production facilities have a role in supporting the smooth production process. By using 9 informants, the results of this study indicate that in Probolinggo Clark King Noodle production facility layout design applied adapted to the stages of the production process. While the maintenance of the machines is done routinely every month for oil changes and cleaning and once a year for a replacement battery and dynamo. And it has launched a noodle production process that took place during this time. Thus has proven that the design layout and maintenance of production facilities is instrumental in supporting a smooth production process that takes place within a manufacturing company.Keywords : Layout Design, Production Facility Maintenance, Production Process